2002
DOI: 10.1016/s0014-5793(02)02321-9
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin‐like receptor binding facilitates proteolytic cleavage of helix α‐1 in domain I and oligomer pre‐pore formation of Bacillus thuringiensis Cry1Ab toxin

Abstract: Cry toxins form lytic pores in the insect midgut cells. The role of receptor interaction in the process of protoxin activation was analyzed. Incubation of Cry1Ab protoxin with a single chain antibody that mimics the cadherin-like receptor and treatment with Manduca sexta midgut juice or trypsin, resulted in toxin preparations with high pore-forming activity in vitro. This activity correlates with the formation of a 250 kDa oligomer that lacks the helix K K-1 of domain I. The oligomer, in contrast with the 60 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
248
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(258 citation statements)
references
References 34 publications
4
248
0
6
Order By: Relevance
“…In the case of the Cry1A toxins, it was reported that they interact sequentially with two protein receptors located in the apical membrane of Manduca sexta larvae midgut cells [3,4]. The interaction of the monomeric Cry1A with the cadherin receptor induces toxin oligomerization [4,5]. The oligomerization of Cry1A toxin increases its affinity to the second receptor, aminopeptidase-N. Aminopeptidase-N localizes the toxin in membrane microdomains, where it is inserted and induces the formation of ionic pores [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the Cry1A toxins, it was reported that they interact sequentially with two protein receptors located in the apical membrane of Manduca sexta larvae midgut cells [3,4]. The interaction of the monomeric Cry1A with the cadherin receptor induces toxin oligomerization [4,5]. The oligomerization of Cry1A toxin increases its affinity to the second receptor, aminopeptidase-N. Aminopeptidase-N localizes the toxin in membrane microdomains, where it is inserted and induces the formation of ionic pores [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…These ionic pores shunt the potential difference gradient and disrupt the K + and H + gradients, affecting nutritional uptake with eventual lysis of the midgut cells [2]. It was proposed that the oligomeric structure of Cry1A toxin is an intermediary in the process of membrane insertion; it is defined as pre-pore since it is formed outside of the membrane after interacting with cadherin and the cleavage of helix a-1 [5]. The pre-pore is an insertion-competent structure that produces stable channels in black lipid bilayers with high open probability in contrast to the monomeric structure [7].…”
Section: Introductionmentioning
confidence: 99%
“…37 The toxin oligomers, usually in dimeric and tetrameric form, are SDS-resistant and could be detected by SDS-PAGE Western blotting. 21,26,38 We were interested in determining whether Cry1Ab interacts with the cytoplasmic membrane of living cells in a similar way, and, if so, whether these interactions contribute to cytotoxicity. Therefore, we analyzed toxin-membrane interactions in S5 and H5 cells by examining protein samples prepared from membrane and cytoplasmic Antibody against Cry1Ab was used to detect the toxin in protein fractions corresponding to membrane pellet (P) and supernatant containing soluble proteins (S).…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25] In the pore-forming model of Cry toxin action, the toxin monomers are considered precursors to oligomeric assembly. 21,25 The formation of toxin oligomer also has been postulated to be the result of the interaction of monomers that were bound to the cadherin receptor. 48 Our results clearly show differential association profiles for the oligomeric and monomeric forms of Cry1Ab toxin in cell membrane, the consequence of two distinct modes of interaction with the insect cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation